Pengamanan Data Teks Dengan NTRU dan Modulus Function pada Koefisien IHWT Citra Warna - Ronsen Purba; Irpan Pardosi; Harry Darmawan; Aldo Alex Sitorus (Fakultas Informatika, 2019)
The development of digital information have caused the rise of information technology security to protect text data that contains secret. Steganography is one of many solutions for securing text data by hiding the text data on an image so that another party would not know the existence of such data. Criteria of a good steganography involves imperceptibility, fidelity, robustness dan recovery. One steganographic method is CD (Coefficient Difference), adopted from PVD (Pixel Value Differencing) which does hiding in spatial domain using difference of two pixel values that results in large modification of pixel values, reducing imperceptibility. Modulus function is used to solve such shortcoming in CD by using the modulus function on embedding, minimizing pixel modification during the process, resulting in improved imperceptibility. In this final project, IHWT (Integer Haar Wavelet Transform) are used to keep imperceptibility high. To improve the security, cryptographic method NTRU is applied on the secret message before it is hidden in image. The result showed that the combination of NTRU, IHWT and modulus function yields good imperceptibility, with PSNR value above 40 dB while the stego image resist salt and pepper noise attack of 0,002% and contrast addition of maximum amount one